Extremely Stochastic Connectivity of Island Mangroves - Thomas, Maki; Nakajima, Yuichi; Mitarai, Satoshi (Frontiers in Marine Science, 2022)
Studies on mangrove population connectivity have focused primarily on global to regional scales and have suggested potential for long-distance connectivity, with archipelagos serving as stepping stones for trans-oceanic dispersal. However, the contribution of propagule dispersal to connectivity is still largely unknown, especially at local-scale. Identifying fine-scale propagule dispersal patterns unique to individual island systems is important to understand their contribution to global species distributions, and to select appropriate sizes and locations for mangrove conservation in archipelagos. Using population genetic methods and a release-recapture method employing GPS drifting buoys, we investigated the spatiotemporal scale of propagule dispersal of Rhizophora stylosa, one of the widely distributed mangrove species in the Indo-West Pacific. This study sought to quantify intra- and inter-island connectivity and to assess their contributions to oceanic scale dispersal of R. stylosa in the Ryukyu Archipelago, which spans over 545 km in southwestern Japan. Using 7 microsatellite markers, we tested 354 samples collected from 16 fringing populations on 4 islands. We identified 3 genetic populations, indicating distinct genetic structures comprising 3 distinguishable bioregions (genetic clusters). The western end of the archipelago receives relatively frequent migration (m>0.1), but is genetically isolated from other sites. Based on genetic migration rates, we found that the central area of the archipelago serves as a stepping stone for southwestward, but not northeastward dispersal. Drifting buoys confirmed the potential for dispersal between islands, and showed predominantly northeastward dispersal. We found that the spatiotemporal scale of propagule dispersal is limited by the distance between islands (<200km), propagule viability duration, local ocean currents, and fecundity. Over all, demographic connectivity does not occur frequently enough to unify the genetic structure in the archipelago, and the Ryukyu Archipelago is isolated among the global mangrove distribution.